Household Size and Income Poverty in Zanzibar - Mkenda, Adolf (Tanzania Journal for Population studies and Development, 2010)
This paper uses the 2004/2005 Zanzibar Household Budget Survey data to probe the relationship between household size and poverty. In doing this the paper ensures that poverty measurement involves adjustment for adult equivalent scales, and that the measures are robust to the variation of poverty line and for a class of poverty indices that satisfies the generally accepted axioms. Further, the paper makes adjustments for economies of scales when measuring poverty at the household level as recommended by Anand and Murdoch (1996). The paper finds that larger households suffer more poverty. However, there is no direction of causality is established, thus it remains unclear whether it is poverty that leads to large household size, or that it is large household size which leads to poverty. A review of literature however indicates that there are economic circumstances that impel poor households to have high fertility rates. However collective impact of high fertility rate is adverse in various ways, including environmental pressure both globally and within the local fragile environment, increased inequality and immiserized growth. This means that at the community, national and global level there are good reasons to find ways to lower fertility rates. This paper further argues that the only way to have a non-coercive and yet effective policy to lower fertility rate is for such policy to seek to alter the economic circumstances that make high fertility a rational choice at the household level; it is not enough to simply make family planning program available to the households.